Chemical engineering kinetics of p-xylene chlorination in a gas-liquid agitated reactor. (16th January 2023) - Rigas, Fotis P.
Graphical abstract: Highlights: A novel approach is proposed for the determination of a reaction rate constant. The method is based on chemical engineering data arranged as a linear equation. The reaction rate of mono-chlorination of p-xylene was determined at 70 and 90 °C. The rate constants up to the tetrachloro product of p-xylene were determined at 70 °C. Many chemical engineering parameters of the chlorination system were also calculated. Abstract: This study aims at determining both the rate constants of chlorination of p-xylene with molecular chlorine and FeCl3 as a catalyst at 70 °C and 90 °C and the related chemical engineering parameters to be used in the design of an effective chemical reactor. This was accomplished by a novel approach of constructing a linear mathematical function for a gas–liquid semi-batch agitated reactor correlating all engaged physical and chemical factors. Collecting values for all the necessary parameters for the application of the function, or in the absence of them calculating them, and exploiting the intercept and slope of the linear function became possible the apparent and the catalytic reaction rate constants to be calculated. It was found that the calculated values were of the same order of magnitude as values obtained by other researchers. The parameters needed to be calculated were Henry's constant, the diffusion coefficient of the solute A (chlorine) to the solvent B (p = xylene), DAB, and the mean liquid phase mass transfer coefficient, kl . Other parameters of chemical engineering interest were also determined, namely, the interface per unit volume of liquid, a, the thickness of the liquid film, δl, and the Hatta number, MH . Evaluating the Hatta number estimated, it was concluded that the chlorination of p-xylene with molecular chlorine is very slow at both temperatures investigated, and almost no reaction occurs in the film compared to the bulk of the liquid. Thus, to increase the overall reaction rate, a large volume of liquid is needed while the increase of agitation intensity is of no value here. Combining the rate constant ratios obtained recently for the four consecutive second-order irreversible chlorinations of p-xylene with molecular chlorine with FeCl3 as a catalyst at 70 °C and under identical conditions it was possible to determine the values of all rate constants up to the fourth chlorinated product.